1996
DOI: 10.1182/blood.v87.4.1532.bloodjournal8741532
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcome of children with first marrow relapse of acute lymphoblastic leukemia expressing BCR-ABL fusion transcripts. BFM Relapse Study Group

Abstract: Although the Philadelphia chromosome (Ph1) has been identified as an adverse prognostic factor in acute lymphoblastic leukemia (ALL), little is known about the incidence and clinical course of relapsed Ph1- positive ALL in children. The incidence was determined by screening of 170 consecutive children with first bone marrow relapse of ALL using the reverse transcriptase-polymerase chain reaction (RT-PCR) and comparison, with cytogenetic analysis. Among these 170 children, 20 (12%) were found to be BCR-ABL-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…More than half of the relapsed patients did not respond to another course of induction chemotherapy. This was consistent with a previous observation [19]. Most patients who achieved a second remission relapsed before the transplantation.…”
Section: Discussionsupporting
confidence: 93%
“…More than half of the relapsed patients did not respond to another course of induction chemotherapy. This was consistent with a previous observation [19]. Most patients who achieved a second remission relapsed before the transplantation.…”
Section: Discussionsupporting
confidence: 93%
“…The 12 patients with Phþve ALL included two with longterm survival, one of whom had received a bone marrow transplant. This abnormality has been detected in a high proportion of relapsed patients (Beyermann et al, 1996) and Phþve ALL does appear to be an indication for bone marrow transplantation in first remission. It may be significant that the two long-surviving children were the only two in the group who also had high hyperdiploidy; it has recently been suggested that patients with this finding have superior survival to others with Phþve ALL (Rieder et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…The prognosis of patients with BCR‐ABL fusion was the worst in childhood ALL [34, 35]. Therefore, in protocols BCH‐2003 and CCLG‐2008, these patients were directly stratified into the high‐risk group.…”
Section: Discussionmentioning
confidence: 99%